Կիրառական մշակութաբանությունը և անձի հոգևոր ձևավորումը - Կարեն Ղազարյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена анализу одной из составных частей культурологического знания - прикладной культурологии. В работе рассматриваются вопросы статуса, содержания прикладной культурологии, характер сопряжения фундаментально-теоретического культурологического знания и прикладного вектора его развития и использования; ряд принципиально важных факторов для реализации творческих дарований личности; возможности прикладной культурологии для решения реальных социокультурных проблем в различных областях деятельности. Опора на прикладную культурологию поможет глубже осмыслить сущность и специфику духовной жизни, внести эстетические начала в повседневную жизнедеятельность. This article is dedicated to the analysis of one of the constituent parts of culturography where questions concerning the status and the subject-matter of the applied culturography are considered. The fundamental-theoretical issues of applied culturography and the essence of relating the development of its application compass to the nature of its utilization are considered as well. The reliance on applied culturography would help exploit the creative aptitude of individuals in a number of essentially important details, solve real socio-cultural problems in different spheres of activities, and also appraise profoundly the essence and distinctive characteristics of spiritual life and introduce the cornerstone of aesthetics into the arena of everyday activities.
Keywords: Culture and Cultural Processes; Social Sciences; Sociology